Coexistence of axial spondyloarthritis and thromboangiitis obliterans in a young woman - G. Lopalco (Reumatismo, 2015)
A peculiar coexistence of axial spondyloarthritis and ischemia of the feet and the fourth finger of the left hand in a young woman, who was a heavy smoker, is discussed in this report. This picture was considered within the context of thromboangiitis obliterans. Positivity of anti-nuclear antibodies and mild elevation of inflammatory parameters were noted. Computed tomography angiograms of upper and lower limbs showed luminal narrowing and occlusion of the left humeral, left anterior/posterior tibial and right anterior tibial arteries. Daily iloprost perfusions were started, and smoking cessation was strongly recommended. Coldness and rest pain in the distal extremities improved within a few weeks. The possibility that spondyloarthritis might precede the clinical picture of thromboangiitis obliterans should be considered in heavy smokers.